t-SNARE dephosphorylation promotes SNARE assembly and exocytosis in yeast - Marash, Michael (Oxford University Press, 2001)
The role of protein phosphorylation in secretion is not well understood. Here we show that yeast lacking the Snc1,2 v-SNAREs, or bearing a temperature-sensitive mutation in the Sso2 t-SNARE, are rescued at restrictive conditions by the addition of ceramide precursors and analogs to the growth medium. Rescue results from dephosphorylation of the Sso t-SNAREs by a ceramide-activated type 2A protein phosphatase (Sit4) involved in cell cycle control. Sso t-SNARE dephosphorylation correlated with its assembly into complexes with the Sec9 t-SNARE, both in vitro and in vivo, and with an increase in protein trafficking and secretion in cells. SNARE complexes isolated under these conditions contained only Sso and Sec9, suggesting that a t–t-SNARE fusion complex is sufficient to confer exocytosis. Mutation of a single PKA site (Ser79 to Ala79) in Sso1 resulted in a decrease in phosphorylation and was sufficient to confer growth to snc cells at restrictive conditions. Thus, modulation of t-SNARE phosphorylation regulates SNARE complex assembly and membrane fusion in vivo.